Rola instytucji kształcenia podstawowego w świetle Ustawy o wspieraniu i resocjalizacji nieletnich - Klawikowska, Maja (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
There are different views on juveniles according to their act of demoralization. The Act on Juvenile Deliquency Proceedings instruct on the measures of aiding families with the upbringing and education of children and teenagers. Every person who notices any antisocial behavior has a duty to stop or prevent the prohibited act and report it to children’s parents, school, or even a family court or law enforcement. If a juvenile commits an offense in relation to the fullfillment of compulsory school attendance, the apply disciplinary measures in a way outlined by the Act.
Keywords: juvenile; resocialization; support; school and family